Material aspects of reading in Ancient and Medieval cultures materiality, presence and performance - Material Aspects of Reading 2018 Heidelberg; Krauß, Anna H. 1988-; Leipziger, Jonas; Schücking-Jungblut, Friederike 1985- (Berlin Boston De Gruyter, 2020)
Frontmatter --Acknowledgements --Contents --Material Aspects of Reading and Material Text Cultures --Material Aspects of Rituals Beyond Their Instructions --Scribal Production and Literacy at Qumran --Scribal Habits and Scholarly Texts --Reading Psalm and Prayer Manuscripts From Qumran --Reading the Songs of the Sabbath Sacrifice --Reading Material Features of Qumran Tefillin and Mezuzot --Reading an Opisthograph at Qumran --Codices des Typs C und die Anfänge des Blätterns --Ancient Jewish Greek Practices of Reading and Their Material Aspects --Reading Early New Testament Manuscripts --What Ancient Christian Manuscripts Reveal About Reading (and About Non-Reading) --Reading Regularly --Encountering the Grotesque --Notes on Contributors --Indices
This publication seeks to endeavour the relationship between material artefacts and reading practices in ancient and medieval cultures. While the acts of reception of written artefacts in former times are irretrievably lost, some of the involved artefacts are preserved and might comprise hints to the ancient reading practices. In form of case studies, the contributions to this volume examine various forms of written artefacts as to their implications on modes of reading. Analyzing different Qumran scrolls, codices, Tefillin, Mezuzot, magical texts, tablets, bricks, and statues as well as meta-textual and iconographic aspects, the articles inquire the possibilities of how to correlate material aspects to assumed modes of reception and practices of reading. The contributions stem from Egyptology, Papyrology, Qumran Studies, Biblical Studies, Jewish Studies, Ancient Christianity, and Islamic Studies. In total, this volume contributes to the research on practices of reception in times past and demonstrates the potential hidden in text-bearing artefacts
In English
Keywords: To 1500; History, Ancient; Manuscripts -- History -- To 1500 -- Congresses; Reading -- History -- To 1500 -- Congresses; Sacred Books -- History -- To 1500 -- Congresses; RELIGION ; Judaism ; History; History, Ancient; Manuscripts; Reading; Sacred Books; Manuscripts - History - To 1500 - Congresses; Reading - History - To 1500 - Congresses; Sacred books - History - To 1500 - Congresses; Conference papers and proceedings; History; Konferenzschrift -- 2018 -- Heidelberg